2019
DOI: 10.1108/ijaim-01-2018-0002
|View full text |Cite
|
Sign up to set email alerts
|

An empirical study of the relationship between accounting conservatism and executive compensation-performance sensitivity

Abstract: Purpose The purpose of this paper is to study the relationship between accounting conservatism and executive compensation-performance sensitivity with a view to identify the influence of accounting conservatism on the efficiency of executive compensation contracts. Design/methodology/approach This study uses multiple regression models based on the approach of Iyengar and Zampelli (2010), Clarkson et al. (2011) and Huang and Kisgen (2013) with the data from all of China’s listed non-financial firms over the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 95 publications
2
11
0
5
Order By: Relevance
“…Several papers have also investigated the relationship between accounting conservatism and executive compensation. Our study is closest in spirit to Zhang et al (2019) who found a significantly positive relationship between accounting conservatism and the executive compensation-performance sensitivity of Chinese listed companies. However, we delineate our study from their study in three ways.…”
Section: Introductionsupporting
confidence: 52%
See 3 more Smart Citations
“…Several papers have also investigated the relationship between accounting conservatism and executive compensation. Our study is closest in spirit to Zhang et al (2019) who found a significantly positive relationship between accounting conservatism and the executive compensation-performance sensitivity of Chinese listed companies. However, we delineate our study from their study in three ways.…”
Section: Introductionsupporting
confidence: 52%
“…Iwasaki et al (2012) find that the asymmetric timeliness of earnings is negatively related to the magnitude of excess compensation. Zhang et al (2019) found a significantly positive relationship between accounting conservatism and the executive compensation-performance sensitivity of Chinese listed companies, particularly for executive compensation contracts where accounting-based performance measure is used. Jeong and Kim (2013) found a positive relationship between equity-based compensation to outside directors and accounting conservatism using the US data between 2006 and 2008.…”
Section: Prior Research and Hypothesis Developmentmentioning
confidence: 91%
See 2 more Smart Citations
“…Female executives can enhance executive pay-performance sensitivities via positively determining accounting conservatism and social responsibility performance. Accounting conservatism has a positive relation with the executives' compensation-performance sensitivity after controlling for critical firmspecific factors and control variables (Zhang et al, 2019) while female executives show higher accounting conservatism than male peers due to their gender nature. Therefore, TMTs with higher ratio of female executives would intend to choose higher executives' compensation-performance sensitivity.…”
Section: Journal Of Social Economics Researchmentioning
confidence: 90%